Hubungan Perfectionism dan Academic Burnout pada Mahasiswa Tingkat Akhir di Jakarta - Adilatun Nisa; Roswiyani Roswiyani; Willy Tasdin (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
This study aims to determine the relationship between perfectionism and academic burnout among final-year students in Jakarta. Academic burnout is defined as stress arising from the learning process that results in emotional exhaustion, depersonalization, and low academic performance (Sagita & Meilyawati, 2021). Perfectionism is considered a personality disposition characterized by concerns about self-evaluation, overly critical self-assessment, and striving to achieve perfect personal standards (Hill, 2017). This study employs a quantitative approach, involving final-year university students in Jakarta aged 20–25 years who are in their 7th–9th semesters. The sampling technique used is purposive sampling. The measurement tools used were the Multidimensional Perfectionism Scale developed by Flett and Hewitt (1991) and the School Burnout Inventory developed by Salmela-Aro, Kiuru, Leskinen, and Nurmi in 2009. The results of the correlation test using Pearson Correlation yielded a value of r = 0.854, with significance 0.000 p < 0.05. These results indicate that there is a relationship between perfectionism and academic burnout among final-year students in Jakarta. Based on the correlation test per dimension, the results show that there is a relationship between perfectionism and all dimensions of academic burnout, especially the exhaustion dimension. Additionally, there is a relationship between academic burnout and all dimensions of perfectionism, particularly the socially prescribed perfectionism dimension. This indicates that the higher an individual's level of perfectionism, the higher their level of academic burnout.